2007
DOI: 10.1007/s00449-007-0153-9
|View full text |Cite
|
Sign up to set email alerts
|

Biologically Fe2+ oxidizing fluidized bed reactor performance and controlling of Fe3+ recycle during heap bioleaching: an artificial neural network-based model

Abstract: The performance of a biological Fe(2+) oxidizing fluidized bed reactor (FBR) was modeled by a popular neural network-back-propagation algorithm over a period of 220 days at 37 degrees C under different operational conditions. A method is proposed for modeling Fe(3+) production in FBR and thereby managing the regeneration of Fe(3+) for heap leaching application, based on an artificial neural network-back-propagation algorithm. Depending on output value, relevant control strategies and actions are activated, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 17 publications
(21 reference statements)
0
7
0
Order By: Relevance
“…In the ANN modelling of CSTR, the procedure given by Ozkaya et al [13] was followed. A neural network is defined as a system of simple processing elements, called neurons, which are connected to a network by a set of weights (Fig.…”
Section: Modellingmentioning
confidence: 99%
“…In the ANN modelling of CSTR, the procedure given by Ozkaya et al [13] was followed. A neural network is defined as a system of simple processing elements, called neurons, which are connected to a network by a set of weights (Fig.…”
Section: Modellingmentioning
confidence: 99%
“…The prediction models such as ANNs demonstrate stronger and more realistic behavior in predicting the complex non-linear and ever changing conditions of biological processes. ANN applications were previously used in some studies to predict the leaching of metals for bioleaching processes with similar or different microorganism groups and sludges from different industries and applications (Du et al, 1994;Acharya et al, 2006;Ozkaya et al, 2008;Liu et al, 2008;Jorjani et al, 2007;Nurmi et al, 2010;Laberge et al, 2000). In this study, a three layer feed forward MLP neural network model was developed to predict the effluent heavy metal concentrations of bioleaching technique involving A. ferrooxidans in dewatered metal plating sludge containing no sulfide or sulfate compounds.…”
Section: Discussionmentioning
confidence: 99%
“…The application of ANN to issues related to wastewater treatment and water resources conservation is rapidly gaining popularity due to their immense power and potential in the mapping of nonlinear system data. In the context of hydrological forecasting, recent studies have reported that ANN technique may offer a promising alternative for bioleaching (Acharya et al, 2006;Ozkaya et al, 2008;Liu et al, 2008;Jorjani et al, 2007;Nurmi et al, 2010;Laberge et al, 2000), rainfall-runoff modeling (Lin and Chen, 2004), stream-flow prediction (Raman and Sunilkumar, 1995;Kisi, 2004a), suspension of sediments (Kisi, 2004b), water resources (Cobaner et al, 2008), reservoir inflow forecasting (Coulibaly et al, 2005) and treatment of wastewater (Elmolla et al, 2010;Pai et al, 2009;Chen and Lo, 2010). The variation in the characteristics of a bioleaching system may be non-linear and multivariate, and the variables involved may have complex inter-relationships.…”
Section: Artificial Neural Network Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…They also modeled the performance of a biological Fe 2+ oxidizing fluidized bed reactor (FBR) by a popular neural network-back-propagation algorithm under different operational conditions [16]. Yetilmezsoy and Demirel used a three-layer artificial neural network (ANN) model to predict the efficiency of Pb(II) ions removal from aqueous solution by Antep pistachio (Pistacia vera L.) shells based on 66 experimental sets obtained in a laboratory batch study [17].…”
Section: Et Al Utilized Ann For Thementioning
confidence: 99%